JEREMIAH 51:15-19 (MT): - M D Terblanche (Acta Theologica)
The oracles against Babylon seem to be an anomaly in the Book of Jeremiah. The doxology in Jeremiah 51:15-19 (MT) does, however, serve as a link between these oracles and the remainder of the book of Jeremiah. By giving the impression of being a deliberate quotation of 10:12-16, 51:15-19 takes the reader back to 10:1-16, a composition in which the contrast between the idols of the nations and YHWH is emphasized. YHWH has the power to execute his plan to destroy Babylon. 51:15-19 did, however, attain a distinct identity through its close connections with the oracles against Babylon. It paradoxically functions as a link between these oracles and those against Judah. In contrast to YHWH’s actions, which resulted in the destruction of Jerusalem, his future dealings would result in the fall of Babylon and the return of his people from exile.